Telehealth Competency Questionnaire-Consumer: Psychometric Validation of a Client-centered Measure - Steven Taylor, PhD, OTR/L; Lauren M. Little, PhD, OTR/L, FAOTA (International Journal of Telerehabilitation)
To effectively access telehealth services, individuals must possess certain competencies; yet, telehealth consumer focused measures are limited. The purpose of this study was to describe the development and validation of the Telehealth Competency Questionnaire – Consumer (TCQ-C). Among a sample of adults with chronic health conditions (n=134), findings showed that the TCQ-C is comprised of one factor that accounts for 66.6% of the variance, and internal consistency of subscales are good (range α = 0.80-0.87) and may be used for clinical or research purposes. The TCQ-C demonstrated moderate concurrent validity with the Telehealth Usability Questionnaire-Usability subscale (r = 0.728, p<.001), and significantly discriminates between adults >65 years and those younger as well as those with and without previous telehealth experience. The TCQ-C is a psychometrically sound instrument to evaluate baseline competencies among telehealth consumers so that education, research, and clinical practices are tailored to increase effective engagement between clients and providers.